Panduratin A Derivative Protects against Cisplatin-Induced Apoptosis of Renal Proximal Tubular Cells and Kidney Injury in Mice - Penjai Thongnuanjan (MDPI AG, 2021)
Background: Panduratin A is a bioactive cyclohexanyl chalcone exhibiting several pharmacological activities, such as anti-inflammatory, anti-oxidative, and anti-cancer activities. Recently, the nephroprotective effect of panduratin A in cisplatin (CDDP) treatment was revealed. The present study examined the potential of certain compounds derived from panduratin A to protect against CDDP-induced nephrotoxicity. Methods: Three derivatives of panduratin A (DD-217, DD-218, and DD-219) were semi-synthesized from panduratin A. We investigated the effects and corresponding mechanisms of the derivatives of panduratin A for preventing nephrotoxicity of CDDP in both immortalized human renal proximal tubular cells (RPTEC/TERT1 cells) and mice. Results: Treating the cell with 10 µM panduratin A significantly reduced the viability of RPTEC/TERT1 cells compared to control (panduratin A: 72% ± 4.85%). Interestingly, DD-217, DD-218, and DD-219 at the same concentration did not significantly affect cell viability (92% ± 8.44%, 90% ± 7.50%, and 87 ± 5.2%, respectively). Among those derivatives, DD-218 exhibited the most protective effect against CDDP-induced renal proximal tubular cell apoptosis (control: 57% ± 1.23%; DD-218: 19% ± 10.14%; DD-219: 33% ± 14.06%). The cytoprotective effect of DD-218 was mediated via decreases in CDDP-induced mitochondria dysfunction, intracellular reactive oxygen species (ROS) generation, activation of ERK1/2, and cleaved-caspase 3 and 7. In addition, DD-218 attenuated CDDP-induced nephrotoxicity by a decrease in renal injury and improved in renal dysfunction in C57BL/6 mice. Importantly, DD-218 did not attenuate the anti-cancer efficacy of CDDP in non-small-cell lung cancer cells or colon cancer cells. Conclusions: This finding suggests that DD-218, a derivative of panduratin A, holds promise as an adjuvant therapy in patients receiving CDDP.